Religiosity and Resilience in Students of the Faculty of Catholic Religious Education - Tindaon, Ronika; Fathiyah, Kartika Nur; Paji, Yohanes Engelbertus (Universitas Ahmad Dahlan, 2024)
The purpose of this study was to determine the effect of religiosity on resilience in college students. This study used a quantitative approach with a correlational research type with a population of 237 pastoral high school students. The sampling technique used was simple random sampling of 108 people. Data collection used a resilience scale with The 14-Item Resilience Scale (RS-14) and a religiosity scale with The Centrality of Religiosity Scale (CRS). The results found that there was a significant influence between religiosity on resilience in college students, with an effective contribution of 64%. Based on the categorization results, the majority of subjects in this study have resilience and religiosity in the moderate category.